Policy options for enhancing economic profitability of residential solar photovoltaic with battery energy storage. (15th May 2021) - Zakeri, Behnam; Cross, Samuel; Dodds, Paul.E.; Gissey, Giorgio Castagneto
Highlights: Pairing solar PV with battery can reduce electricity imports from the grid by up to 84%. Home battery doubles PV self-consumption in the building. Rewarding self-consumption of PV is the most effective policy for mobilizing onsite flexibility solutions like batteries. Solar PV paired with battery can be profitable for residential consumers even in high-latitude countries. Value of arbitrage for residential electricity storage can be three times higher than utility-scale storage. Abstract: Share of solar photovoltaic (PV) is rapidly growing worldwide as technology costs decline and national energy policies promote distributed renewable energy systems. Solar PV can be paired with energy storage systems to increase the self-consumption of PV onsite, and possibly provide grid-level services, such as peak shaving and load levelling. However, the investment on energy storage may not return under current market conditions. We propose three types of policies to incentivise residential electricity consumers to pair solar PV with battery energy storage, namely, a PV self-consumption feed-in tariff bonus; "energy storage policies" for rewarding discharge of electricity from home batteries at times the grid needs most; and dynamic retail pricing mechanisms for enhancing the arbitrage value of residential electricity storage. We soft-link a consumer cost optimization model with a national power system model to analyse the impact of the proposed policies on the economic viability of PV-storage for residential end-users in the UK. The results show that replacing PV generation incentives with a corresponding PV self-consumption bonus offers return on investment in a home battery, equal to a 70% capital subsidy for the battery, but with one-third of regulatory costs. The proposed energy storage policies offer positive return on investment of 40% when pairing a battery with solar PV, without the need for central coordination of decentralized energy storage nor providing ancillary services by electricity storage in buildings. We find that the choice of optimal storage size and dynamic electricity tariffs are key to maximize the profitability of PV-battery energy storage systems.